Scripture as real presence : sacramental exegesis in the early church - Boersma, Hans, 1961- (Grand Rapids, MI. Baker Academic, 2017)
This work argues that the heart of patristic exegesis is the attempt to find the sacramental reality (real presence) of Christ in the Old Testament Scriptures. Leading theologian Hans Boersma discusses numerous sermons and commentaries of the church fathers to show how they regarded Christ as the treasure hidden in the field of the Old Testament and explains that the church today can and should retrieve the sacramental reading of the early church. Combining detailed scholarly insight with clear, compelling prose, this book makes a unique contribution to contemporary interest in theological interpretation.
1. Patristic reading : The church fathers on sacramental reading of Scripture -- 2. Literal reading : Gregory of Nyssa and Augustine on the creation accounts of Genesis -- 3. Hospitable reading : Origen and Chrysostom on the theophany of Genesis 18 -- 4. Other reading : Melito of Sardis and Origen on the Passover of Exodus 12 -- 5. Incarnational reading : Origen on the historical narrative of Joshua -- 6. Harmonious reading : Clement of Alexandria, Athanasius, Basil, Gregory of Nyssa, and Augustine on the music of the Psalms -- 7. Doctrinal reading : Athanasius and Gregory of Nyssa on the wisdom of Proverbs 8 -- 8. Nuptial reading : Hippolytus, Origen, and Ambrose on the bridal couple of the Song of Songs -- 9. Prophetic reading : Irenaeus, Cyril of Alexandria, Origen, Eusebius, Gregory of Nyssa, Jerome, Ambrose, and Augustine on the servant songs of Isaiah -- 10. Beatific reading : Gregory of Nyssa, Augustine, and Leo the Great on the Beatitudes of Matthew 5.
Includes bibliographical references (p. 280-298) and indexes.
Keywords: Bible. -- Criticism, interpretation, etc. -- History -- Early church, ca. 30-600.; Sacraments -- History of doctrines -- Early church, ca. 30-600.